Engineering Growth: Innovative Capacity and Development in the Americas - William F. Maloney; Felipe Valencia Caicedo (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper offers the first systematic historical evidence on the role of a central actor in modern growth theory - the engineer. It collects cross-country and state level data on the labor share of engineers for the Americas, and county level data on engineering and patenting for the US during the Second Industrial Revolution. These are robustly correlated with income today after controlling for literacy, other types of higher order human capital (e.g. lawyers, physicians), demand side factors, and after instrumenting engineering using the Land Grant Colleges program. A one standard deviation increase in engineers in 1880 accounts for a 16% increase in US county income today, and patenting capacity contributes another 10%. We further show engineering density supported technological adoption and structural transformation across intermediate time periods. Our estimates help explain why countries with similar levels of income in 1900, but tenfold differences in engineers diverged in their growth trajectories over the next century. The results are supported by historical case studies from the US and Latin America.
Keywords: O11; O30; N10; I23; 330; innovative capacity; human capital; engineers; technology diffusion; patents; growth; structural transformation; development; history